ANALYSIS OF HIGH SCHOOL STUDENTS’ MATHEMATICAL REFLECTIVE THINKING ABILITY IN SOLVING THREE-VARIABLE LINEAR EQUATION WORD PROBLEMS - Widya Nurmalia Fatma; Hanifah Hanifah; Lessa Roesdiana (Universitas Sembilanbelas November Kolaka, 2026)
Mathematical reflective thinking is an essential ability that enables students to understand problems, connect prior knowledge, evaluate solution strategies, and justify their conclusions. This study aims to analyze high school students’ mathematical reflective thinking ability in solving three-variable linear equation word problems. This research employed a descriptive method with a qualitative approach supported by quantitative descriptive analysis. The subjects were 33 eleventh-grade students from a senior high school in Karawang Regency. Data were collected through three essay questions designed based on three indicators of mathematical reflective thinking: reacting, comparing/elaborating, and contemplating. The results showed that students’ mathematical reflective thinking ability was not yet fully developed. Based on the categorization, 9.1% of students were in the high category, 72.7% were in the medium category, and 18.2% were in the low category. The analysis of students’ responses indicated that students were generally able to identify some information in the problems, but many still experienced difficulties in constructing mathematical models, selecting appropriate solution strategies, and verifying the correctness of their answers. These findings suggest that students need learning activities that encourage deeper reflection, systematic problem solving, and evaluation of mathematical reasoning.